Pendampingan Ibadah Masyarakat Melalui Kegiatan Sholat Malam dan Istighotsah Pada Malam Ganjil 10 Akhir Ramadhan NU Ranting Bulu - Miftahuddin Miftahuddin; Roudhotul Jannah (ABDIMASY: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program (PKM) aims to enhance the quality of worship and spiritual awareness of the community through mentoring activities in night prayers (qiyamul lail) and istighotsah during the odd nights of the last ten days of Ramadan. The program was conducted in Bulu Village using a participatory and educational approach, actively involving community members in all activities. The implementation took place at 24:00 WIB across several mosques in different hamlets through a rotational system on the 21st, 23rd, 25th, 27th, and 29th nights of Ramadan. The activities included salat tasbih, salat hajat, prostration of gratitude (sujud syukur), and istighotsah performed collectively.The results indicate a significant increase in community participation, rising from approximately 500 participants on the 21st night to about 700 participants on the 29th night, representing a 40% increase. This growth reflects an improvement in community awareness and enthusiasm in observing the blessed nights of Ramadan. Furthermore, the program contributed to enhancing the quality and understanding of worship practices, fostering collective worship habits, and strengthening social cohesion (ukhuwah Islamiyah) within the community.In conclusion, community-based religious mentoring through night prayer and istighotsah activities has proven to be effective in improving spiritual engagement and optimizing the role of mosques as centers of religious and social development at the village level.